New-onset autoantibodies to selenoprotein P following severe burn injury - Turan, Tabael L.; Klein, Holger J.; Graf, Theresia Reding; Chillon, Thilo Samson; Plock, Jan A.; Schomburg, Lutz (Frontiers in Immunology, 2024)
The liver-derived selenium (Se) transporter selenoprotein P (SELENOP) declines in critical illness as a negative acute phase reactant and has recently been identified as an autoantigen. Hepatic selenoprotein biosynthesis and cotranslational selenocysteine insertion are sensitive to inflammation, therapeutic drugs, Se deficiency, and other modifiers. As severe burn injury induces a heavy inflammatory burden with concomitant Se depletion, we hypothesized an impairment of selenoprotein biosynthesis in the acute post-burn phase, potentially triggering the development of autoantibodies to SELENOP (SELENOP-aAb). To test this hypothesis, longitudinal serum samples from severely burned patients were analyzed over a period of six months. Newly occurring SELENOP-aAb were detected in 8.4% (7/83) of the burn patients, with onset not earlier than two weeks after injury. Prevalence of SELENOP-aAb was associated with injury severity, as aAb-positive patients have suffered more severe burns than their aAb-negative counterparts (median [IQR] ABSI: 11 [7-12] vs. 7 [5.8-8], p = 0.023). Autoimmunity to SELENOP was not associated with differences in total serum Se or SELENOP concentrations. A positive correlation of kidney-derived glutathione peroxidase (GPx3) with serum SELENOP was not present in the patients with SELENOP-aAb, who showed delayed normalization of GPx3 activity post-burn. Overall, the data suggest that SELENOP-aAb emerge after severe injury in a subset of patients and have antagonistic effects on Se transport. The nature of burn injury as a sudden event allowed a time-resolved analysis of a direct trigger for new-onset SELENOP-aAb, which may be relevant for severely affected patients requiring intensified acute and long-term care.